Melacak Akar Kreativitas di Kota Bandung Masa Kolonial - Sunjayadi, Achmad (UI Scholars Hub, 2020)
In 2007 Bandung was designated as a pilot project for the creative cities of Asia Pacific, and in 2015 Bandung was included in the UNESCO Creative Cities Network. It is related to the development of the city of Bandung and the creativity of the population. Its creativity is formed through a process. This article traces the roots of this creativity since the beginning of its formation in the early 19th century to become the city of Bandung in the early 20th century. The method used is the historical method supported by creative cities’ and voluntary organization’s concepts. Primary sources were official government archives, tourist guidebooks, magazines, and newspapers. The result shows that the roots of the creativity of the Bandung population have been formed since the colonial period, both individually and in groups. Through the synergy between the community and leaders in the city of Bandung, they are incorporated into organizations whose initial goals are for the welfare of the people of Bandung, then develop introducing the city of Bandung for people from outside Bandung in tourism activities. They prepared several infrastructure facilities and built tourism objects for both citizens and tourists.